The Impact of Advanced Teaching Tools on Uni-versity Teachers' Adoptive Intention in Sichuan in the Age of Artifi-cial Intelligence - Yong Zhao; Jacky Mong Kwan Watt (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
The Impact of Advanced Teaching Tools on University Teachers' Adoptive Intention in Sichuan in the Age of Artificial Intelligence" explores the significant relationship between innovative teaching tools and university educators' willingness to integrate artificial intelligence technologies into their practices. The study highlights that educators’ positive experiences with advanced teaching tools enhance their perceptions of usability and effectiveness, leading to a greater intention to adopt these technologies. It also examines the role of supportive artificial intelligence policies, which promote ethical usage and provide necessary training, as crucial factors influencing adoption. The findings suggest that fostering an environment that encourages innovative practices and addresses concerns about AI tools can significantly improve educational outcomes. Overall, the research underscores the importance of strategic institutional support in facilitating the successful integration of AI technologies in higher education through a sample of 395 university teachers in Sichuan.